Introducing and Development of Cassava Rengginang MSMEs “Bu Tarni” Pagerukir Village: NIB and Halal Certification - Setiyawan, Doni; Nurhidayat, Saiful; Saputri, Frensiska; Setyawidyastuti, Mey; Cahyani, Adelia (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
The surge in micro, small, and medium-sized enterprises (MSMEs) highlights their vital role in Indonesia's economy by generating employment and fostering innovation. Despite the introduction of the NIB (Business Identification Number) system to streamline business registration, many micro and small entrepreneurs lack the knowledge to obtain necessary business licenses and halal certification. This study focuses on educating and assisting Rengginang cassava entrepreneurs, specifically "Bu Tarni," in Pagerukir Village to navigate these processes. Conducted in August 2023, this initiative involves direct outreach and guidance to facilitate the acquisition of free halal certification through SiHalal and business registration numbers. The project aims to enhance MSMEs' understanding of the significance and procedures of obtaining these certifications, thereby boosting product quality, consumer trust, and sales. The expected outcomes include heightened awareness, improved procedural knowledge, and successful registration and certification of MSMEs, ultimately leading to increased consumer interest and improved community welfare in Pagerukir Village, Sampung District, Ponorogo Regency.